2018
DOI: 10.17222/mit.2018.145
|View full text |Cite
|
Sign up to set email alerts
|

Nitrides and carbides in 2101 lean duplex stainless steel

Abstract: The 2101 lean duplex stainless steel (LDX) was designed mainly for lightweight constructions and as a more economical substitute for the dominating stainless-steel grades. Compared with other duplex stainless steels, the corrosion resistance and costs of processing the 2101 duplex stainless steel are usually worse, as the Ni and Mo contents are lower; it is compensated by higher N and Mn contents to stabilize the austenite. At lower test temperatures the precipitation of different phases was observed, so diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…A typical microstructure of the γ phase (austenite) distributed in the matrix of the δ phase (δ-ferrite) was observed. An analogous structure after hot rolling of lean duplex LDX2101 steel was observed by G. Ubertalli et al [34], F. Iacoviello et al [35], W. Gong et al [36], F. Tehovnik [37] or S. Gudikandula, and A. Sharma [38]. Changes in the microstructure after annealing at 800 °C are shown in Figure 2.…”
Section: Microstructure Of the Base Materialssupporting
confidence: 74%
See 2 more Smart Citations
“…A typical microstructure of the γ phase (austenite) distributed in the matrix of the δ phase (δ-ferrite) was observed. An analogous structure after hot rolling of lean duplex LDX2101 steel was observed by G. Ubertalli et al [34], F. Iacoviello et al [35], W. Gong et al [36], F. Tehovnik [37] or S. Gudikandula, and A. Sharma [38]. Changes in the microstructure after annealing at 800 °C are shown in Figure 2.…”
Section: Microstructure Of the Base Materialssupporting
confidence: 74%
“…It was also indicated that the molybdenum content at a level lower than 0.35% causes the nucleation and growth of the σ phase to be slow/delayed and the formation of M 7 C 3 and M 23 C 6 type carbides is the least possible. Finally, Tehovnik et al [37] showed in TEM and SEM-EBSD observation that after heat treatment of 800 • C/120 min, chromium nitrides, Cr 2 N, and a small amount of M 23 C 6 carbides are observed on the grain boundaries. It should be noted, however, that the tested alloy contained 0.32%Mo, which could facilitate the precipitation of this carbide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5–7 ] Economic duplex stainless steel is regarded as the future development trend as expensive Ni is replaced with cheap Mn and N elements without deteriorating its corrosion resistance significantly. [ 8,9 ] The corrosion resistance (especially pitting corrosion) of 2101 duplex stainless steel, a typical economic duplex stainless steel, attracts lots of attention currently. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Higher level of alloying of advanced DSS leads to the precipitations of undesirable secondary phases, in particular the σ-phase [7] and chromium nitrides [8]. Other secondary phases such as chromium carbides [9] and/or carbonitrides of microalloying elements [10] can also affect the properties of these steels, but the negative effect of the σ-phase and chromium nitrides is predominant [7][8].…”
Section: Introductionmentioning
confidence: 99%